Transgenic Analyses of Homer2 Function Within Nucleus Accumbens Subregions in the Regulation of Methamphetamine Reward and Reinforcement in Mice - Brown, Chelsea N.; Fultz, Elissa K.; Ferdousian, Sami; Rogers, Sarina; Lustig, Elijah; Page, Ariana; Shahin, John R.; Flaherty, Daniel M.; Von Jonquieres, Georg; Bryant, Camron D.; Kippin, Tod E.; Szumlinski, Karen K. (Frontiers in Psychiatry, 2020)
Problems associated with the abuse of amphetamine-type stimulants, including methamphetamine (MA), pose serious health and socioeconomic issues world-wide. While it is well-established that MA’s psychopharmacological effects involve interactions with monoamine neurotransmission, accumulating evidence from animal models implicates dysregulated glutamate in MA addiction vulnerability and use disorder. Recently, we discovered an association between genetic vulnerability to MA-taking and increased expression of the glutamate receptor scaffolding protein Homer2 within both the shell and core subregions of the nucleus accumbens (NAC) and demonstrated a necessary role for Homer2 within the shell subregion in MA reward and reinforcement in mice. This report extends our earlier work by interrogating the functional relevance of Homer2 within the NAC core for the conditioned rewarding and reinforcing properties of MA. C57BL/6J mice with a virus-mediated knockdown of Homer2b expression within the NAC core were first tested for the development and expression of a MA-induced conditioned place-preference/CPP (4 pairings of 2 mg/kg MA) and then were trained to self-administer oral MA under operant-conditioning procedures (5-80 mg/L). Homer2b knockdown in the NAC core augmented a MA-CPP and shifted the dose-response function for MA-reinforced responding above control levels. To determine whether Homer2b within NAC subregions played an active role in regulating MA reward and reinforcement, we characterized the MA phenotype of constitutive Homer2 knockout (KO) mice and then assayed the effects of virus-mediated over-expression of Homer2b within the NAC shell and core of wild-type and KO mice. In line with the results of NAC core knockdown, Homer2 deletion potentiated MA-induced CPP, MA-reinforced responding and intake, as well as both cue- and MA-primed reinstatement of MA-seeking following extinction. However, there was no effect of Homer2b over-expression within the NAC core or the shell on the KO phenotype. These data provide new evidence indicating a globally suppressive role for Homer2 in MA-seeking and -taking but argue against specific NAC subregions as the neural loci through which Homer2 actively regulates MA addiction-related behaviors.